Management of nitrogen-rich legume cover crops as mulch in traditional olive orchards - Ferreira, Isabel Q. (2017)
A low-input agricultural system needs a natural source of nitrogen (N). Legume species can fix great amounts of N that can be subsequently used by a nonlegume crop. In this study three legume cover crops were grown in traditional olive orchards in northeastern Portugal from October 2009 to May 2010, and the aboveground biomass was mechanically destroyed and left on the ground as a mulch. In the following growing season, from October 2010 to May 2011, two nitrophilic plant species were grown in circular microplots of 154 mm surrounded by polyvinyl chloride rings to assess the soil N availability. The N fixed by the legume cover crops, estimated by the difference technique, was shown to vary from 79.7 to 187.5 kg N ha−1. The nitrophilic plant species identified a small peak of soil available N in the autumn of 2010, probably resulting from the mineralization of the root system of the legume species. In the next spring, the increase of soil-available N in the plots where the legume cover crops had been grown, in comparison to the control plot, was residual. The great amounts of N present in the mulched materials seem to disappear without having entered the soil. Mulching with high-N content biomass may be troublesome due to the high risk of N losses probably by ammonia (NH3) volatilization. Copyright © Taylor & Francis Group, LLC.